2021
DOI: 10.1039/d0sm01928c
|View full text |Cite
|
Sign up to set email alerts
|

Orienting and shaping organic semiconductor single crystals through selective nanoconfinement

Abstract: Nanoconfining scaffolds can be used to orient and shape organic semiconductor crystals during solution-phase crystallization depending on the scaffold geometry and the native crystal growth habit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Using sol vents as media, various solutionbased techniques were devel oped to control or confine the flow or evaporation direction of the molecule containing solvents, which in return results in manipulating the crystallographic order of OSC molecules. [18][19][20][21][22] For example, Bao et al demonstrated a shearing force to con trol the contraction direction of the threephase contact line of the solution, so as to guide the assembly of molecule along the moving direction of the scraper. [23,24] Dip coating also pro vides an effective process to control the direction of crystal pre cipitation by withdrawing the substrate from the solution that containing the object materials.…”
Section: Introductionmentioning
confidence: 99%
“…Using sol vents as media, various solutionbased techniques were devel oped to control or confine the flow or evaporation direction of the molecule containing solvents, which in return results in manipulating the crystallographic order of OSC molecules. [18][19][20][21][22] For example, Bao et al demonstrated a shearing force to con trol the contraction direction of the threephase contact line of the solution, so as to guide the assembly of molecule along the moving direction of the scraper. [23,24] Dip coating also pro vides an effective process to control the direction of crystal pre cipitation by withdrawing the substrate from the solution that containing the object materials.…”
Section: Introductionmentioning
confidence: 99%
“…We previously observed such scaffold-directed nanowire formation in organic semiconducting triisopropylsilylethynyl pyranthrene and perylene crystals. When nucleation occurs within the scaffold, nuclei oriented with their fast growth direction parallel to the unconfined direction of the nanopore achieve the critical nucleus size more quickly than misoriented nuclei, resulting in preferential orientation of nanoconfined crystals .…”
Section: Resultsmentioning
confidence: 90%
“…107,158 In nanoconfined spaces, such as the cylindrical nanopores of anodized aluminum oxide scaffolds, crystals tend to grow with the fast growth direction parallel to the long axis of the nanopore. 159,160 We have previously demonstrated the scaffold-directed solution-phase crystallization of semiconducting triisopropylsilylethynyl pyranthrene, 161 perylene 162,163 and formamidinium lead iodide. 164 Organic semiconductors infiltrated into anodized aluminum oxide scaffolds from the melt likewise preferentially orient with the fast growth direction parallel to the long axes of the confining pores.…”
Section: ■ Future Directionsmentioning
confidence: 99%
“… Promoting crystal growth perpendicular to the substrate surface is thus expected to amplify many of the emergent properties discussed in this perspective, including CR, CE, and CPL. One strategy for orienting the fibril growth direction perpendicular to the substrate surface is through the use of nanoconfining scaffolds. , In nanoconfined spaces, such as the cylindrical nanopores of anodized aluminum oxide scaffolds, crystals tend to grow with the fast growth direction parallel to the long axis of the nanopore. , We have previously demonstrated the scaffold-directed solution-phase crystallization of semiconducting triisopropylsilylethynyl pyranthrene, perylene , and formamidinium lead iodide . Organic semiconductors infiltrated into anodized aluminum oxide scaffolds from the melt likewise preferentially orient with the fast growth direction parallel to the long axes of the confining pores .…”
Section: Future Directionsmentioning
confidence: 99%